Decolonization of asymptomatic carriage of multi-drug resistant bacteria by bacteriophages? - Bonnet, Mehdi; Eckert, Catherine; Tournebize, Régis (Frontiers in Microbiology, 2023)
Antimicrobial resistance is a major threat to human and animal health and accounted for up to 4.5 million deaths worldwide in 2019. Asymptomatic colonization of the digestive tract by multi-drug resistant (multi-resistant) bacteria such as extended-spectrum beta-lactamase-, or carbapenemase-producing Enterobacterales is (i) a risk factor for infection by these multiresistant bacteria, (ii) a risk factor of dissemination of these multi-resistant bacteria among patients and in the community, and (iii) allows the exchange of resistance genes between the bacteria. Hence, decolonization or reduction of the gastrointestinal tract colonization of these multi-resistant bacteria needs to be urgently explored. Developing new non-antibiotic strategies to limit or eradicate multi-resistant carriage without globally disrupting the microbiota is considered a priority to fight against antibiotic resistance.Probiotics or Fecal Microbiota Transplantation are alternative strategies to antibiotics that have been considered to decolonize intestinal tract from MDR but there is currently no evidence demonstrating their efficacy. Lytic bacteriophages are viruses that kill bacteria and therefore could be considered as a promising strategy to combat antibiotic resistance. Successful decolonization by bacteriophages has already been observed clinically. Here, we discuss the current alternative strategies considered to decolonize the digestive tract of multi-drugs resistant bacteria, briefly describing probiotics and fecal microbiota transplantation approaches, and then detail the in vivo and in vitro studies using bacteriophages, while discussing their limits regarding the animal models used, the characteristics of phages used and their activity in regards of the gut anatomy.